Construção e validação do conteúdo de uma tecnologia educacional audiovisual para gestantes com síndromes hipertensivas - Almeida, Denise Comin Silva (2024)
Introduction: Maternal mortality in Brazil and worldwide is a serious public health and social problem. Mortality rates have not yet reached the levels of the Sustainable Development Goals and the main causes are hypertensive syndromes related to the pregnancy-puerperal period. Faced with this problem, it is important to strengthen education and health promotion actions so that pregnant women can be autonomous in their self-care process. Objective: To build and validate the content of an audiovisual educational technology for health promotion and education aimed at pregnant women with hypertensive syndromes. Methodology: This is a methodological study to build and validate the content of a video, guided by the stages of the ADDIE Model of Instructional Design. The first stage included context analysis, in which literature review studies and qualitative field research were carried out in order to determine the gaps in knowledge on the subject and the needs of the target audience (hypertensive pregnant women). This was followed by the Design and Development stages, where the script and storyboard for the video were constructed. Once completed, the content was subjected to content validation by expert judges. A Likert-type scale was used to measure the relevance of the items presented. This project was approved by the Research Ethics Committee of the Federal University of Santa Maria under opinion number: 5.824.085. Results: The literature review and field research made it possible to recognize the needs of hypertensive pregnant women regarding the theoretical content of the educational technology as well as what type of technology should be built in order to achieve greater interest and use. The content and storyboard were developed with the support of the Educational Technology Coordination Office at the Federal University of Santa Maria and was validated by 19 expert judges, 100% of whom were nurses with postgraduate degrees at master's and doctorate level. The overall content validity index was 0.92, showing significant agreement between the judges for the items analyzed. Final considerations: The content of the educational technology in question was considered valid for the purposes of education and health promotion for pregnant women with hypertensive syndromes. It is expected to make an important contribution to reducing maternal morbidity and mortality, as pregnant women understand the importance of self-care and are strengthened by correct information about their gestational health and the measures to be taken in good time. We also suggest continuing the study by completing the video, implementing it and evaluating it with the target audience.